E-LEARNING BERBASIS SCHOOLOGY PADA PEMBELAJARAN MATEMATIKA SD - Ariani, Yetti; Helsa, Yullys; Zainil, Melva (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
The purpose of this study is to develop digital class learning models using social learning network Schoology in elementary mathematics learning that is practical, valid and effective so that it can improve the quality of learning being carried out. This study focuses on designing learning tools used in digital classes in elementary schools, learning frameworks are expected to be valid and practical and effective. This research development uses the ADDIE model. Targeted outputs in research are digital class learning models using social learning network workogy and learning tools in the form of lesson plans, student activity sheets, student books, teacher books, and learning assessments. Digital class learning models using social learning netrwork schoology are targeted to be valid, practical, and effective in increasing the competency of elementary school students. In addition to learning models and tools, research output targets are JME (Journal on Mathematics Education / Scopus) international journals, accredited national journals namely International of Trends in Mathematics Education Research (IJTMER), proceedings of international seminars Journal of Physics and Astronomy, and proceedings of national seminars . The proposed level of technological readiness (TKT) of the proposed research is 3. The target of the TKT to be achieved in this study is 4. The results of the study can add references about models and learning tools for Digital Class.